PBL PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PENINGKATAN KETERAMPILAN PASSING PADA PERMAINAN FUTSAL SISWA MI ASSALAM SUMEDANG: PENGARUH MODEL PEMBELAJARAN PBL TERHADAP PENINGKATAN PASSING PADA PERMAINAN FUTSAL SISWA MI ASSALAM SUMEDANG - Firjatullah, Luthfi Resa; Muhtar, Tatang; Alif, Muhammad Nur (Jurnal Porkes, 2025)
This study aims to analyze the effect of the problem-based learning model on improving passing skills in futsal games. The background of this study is based on the low passing skills of students in futsal games and the lack of variety in learning methods applied by sports teachers, which causes students to feel bored and unmotivated. This study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The population in this study were 99 students, and the sample was taken as many as 30 students with purposive sampling technique. The instrument used was a passing skill test with cardboard target media. Data were collected through observation, interviews, and pretest and posttest, then analyzed using SPSS version 22 with various statistical tests, including normality test, paired sample t-test, and independent sample t-test. The average passing score of the PBL model increased from 56.67 in the pretest to 83.67 in the posttest. In contrast, the conventional method only increased from 55.33 to 69.67. The paired sample t-test test resulted in a significance value of 0.000 < 0.05, which indicated a significant increase in the experimental group before and after treatment. The conclusion is that there is a significant effect of applying the PBL model on improving students' passing skills.